Stump Appendicitis in Two Adolescent Boys: Rare Presentations and Alternative Approaches in Pediatrics - Ferreira de Lima, S (2020)
Stump appendicitis is a rare complication that results from reinflammation of the residual part of the appendix, after incomplete appendectomy. Factors that may contribute to inadequate identification of appendicular base are subserosal or retrocecal position, extensive inflammation or inadequate surgical exposure. The length of the appendiceal stump after ligation is likely a major predisposing factor. The presentation of stump appendicitis is similar to acute appendicitis, but this diagnosis is often dismissed because of the surgical history. Computed tomography and ultrasonography are the imaging modalities of choice. The usual recommended treatment for stump appendicitis is completion appendectomy. Stump appendicitis must be considered in the differential diagnosis of acute abdomen despite the patient’s appendectomy history. A delayed diagnosis may lead to an increase in morbidity. We present two cases of stump appendicitis in adolescents after laparoscopic appendectomies, one being a case of recurrent stump appendicitis. We report two alternative therapeutic approaches: interval appendectomy and non-operative management. We conclude that these alternative approaches may be suitable for some patients with stump appendicitis. A review of the pertinent literature was done.